On The Balcony, Beyond “Balconearing”; Perception of Cairene Women, Behind The Curtains. - Al-Gebeily, Rowida Magdy (AUC Knowledge Fountain, 2023)
This study sheds light on the significance and role of threshold spaces as means of accomplishing sociocultural needs, restoration and wellbeing in the residential environment. Understanding the function and uses of these spaces allows us to appreciate their benefits that are often neglected. The research particularly focuses on the social dimension of one fundamental threshold space; the Cairene balcony. It is an integral space that provides a valuable connection to the outside, and its importance in the development of urban living is widely recognized. If carefully designed to meet the residents’ needs and demands, they can promote a better quality of life in the residential environment. Nonetheless, as of today, balconies are eliminated from house designs and when present, they are usually small or inconvenient for the occupants. Accordingly, this study targets the ‘everydayness’ of space use in Egyptian culture and the role played by balconies in Cairene homes. The study examines the performance and perception of balconies and the variables affecting the frequency/ intensity of their usage. It proceeds with the core question; ‘What is the role of the balcony in the Egyptian context, as perceived by local women?’A qualitative anthropological approach was adopted in this research where non-participatory observation was conducted across three local contexts in Egypt, and was followed by in depth interviews (n = 46) with female residents. The selected contexts represent an informal urban neighborhood, old urban neighborhood and a new planned neighborhood, where women came from the middle and low income groups. Key questions addressed the day to day uses of the balconies, the various modifications conducted to satisfy personal needs, and the capacity of the balcony space to accommodate for the various uses. Results disclosed what kind of features, contextual characteristics/exposure (main street, side street, etc.) promote or inhibit balcony usage. Irrespective of the income group, sociocultural background and context, dominating factors influencing women’s perception on the role of the Cairene balcony were commonly present. These included issues of; privacy and control, safety and security, wellbeing and restoration, functional and communicative purposes and the phenomenon of personalization and identity. Overall, as perceived by local women, the balcony contributes to significant ‘safety, restorative, functional, festive, and adaptive roles’. The majority of women stressed on the significance of the balcony as a prominent source of prospect and an impermissible part of the residential environment.